2019
DOI: 10.1039/c9ce01187k
|View full text |Cite
|
Sign up to set email alerts
|

Natural and synthetic metal oxalates – a topology approach

Abstract: Network topology analysis is applied to a large number of mineral and synthetic oxalates, and is shown to be a superior method in describing and communicating the structure of these materials, including the first natural MOF weddellite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Though not described before, the laf-net can be found in the ToposPro 26 The laf-net has large rectangular channels running in two directions, and we speculate that larger cations, not fitting into the space in the kgd-nets, might template this network just as some larger cations induce the srs and other 3D-nets in the tris-oxalate-based systems. 24,25,27 The Concept of Foldable Nets. Inspecting the physical model in Figure 5, we noted that this net can be "folded" along the tetragonal axis while the individual hexagonal and trigonal geometries stay exactly the same; see Figure 7.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Though not described before, the laf-net can be found in the ToposPro 26 The laf-net has large rectangular channels running in two directions, and we speculate that larger cations, not fitting into the space in the kgd-nets, might template this network just as some larger cations induce the srs and other 3D-nets in the tris-oxalate-based systems. 24,25,27 The Concept of Foldable Nets. Inspecting the physical model in Figure 5, we noted that this net can be "folded" along the tetragonal axis while the individual hexagonal and trigonal geometries stay exactly the same; see Figure 7.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In terms of chirality, these versions of the kgd-net with trisbischelating octahedral metal centers share some features with the honeycomb (hcb) nets constructed from tris-oxalate coordination entities. 24,25 The latter contain alternating Δ or Λ enantiomers of the metal complexes, and in all examples of the kgd-net with tris-bischelating octahedral metal centers (MOF-888, CTH-7, CTH-10, Zn-MOF-888, CTH-11) we also in each layer see alternating clockwise propellers for the cpb ligand and anticlockwise for the likewise propeller-shaped metal complex (and vice versa). This is always matched by the opposite chirality in the next layer.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…COD is characterized by a zeolitic structure exhibiting a true structural challenge. It is considered as one of the very few natural MOFs (Metal Organic Frameworks) (Huskic, 2016;Dazem et al, 2019) and its chemical formula is better represented by CaC2O4 . (2+x)H2O (x ≤ 0.5) (Petit et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…and minerals [35,36]. Additionally, the use of this ligand in combination with Ln and An metals as a toolbox to obtain CPs dates back to the 1980s, where Kahwa et al [37] reported a family of isostructural 1D structures with the general formula K 3 [Ln(ox) 3 (OH 2 )]•2H 2 O, (Ln = Nd, Sm, Eu, Gd, Tb).…”
Section: Coordination Polymers Based On Oxalate Linkermentioning
confidence: 99%